Catalyst Initiation in the Oscillatory Carbonylation Reaction - Katarina Novakovic; Julie Parker (International Journal of Chemical Engineering)
Palladium(II) iodide is used as a catalyst in the phenylacetylene oxidative carbonylation reaction that has demonstrated oscillatory behaviour in both pH and heat of reaction. In an attempt to extract the reaction network responsible for the oscillatory nature of this reaction, the system was divided into smaller parts and they were studied. This paper focuses on understanding the reaction network responsible for the initial reactions of palladium(II) iodide within this oscillatory reaction. The species researched include methanol, palladium(II) iodide, potassium iodide, and carbon monoxide. Several chemical reactions were considered and applied in a modelling study. The study revealed the significant role played by traces of water contained in the standard HPLC grade methanol used.